2014
DOI: 10.1007/s10552-014-0436-9
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: The ‘obesity paradox’ and survival after colorectal cancer: true or false?

Abstract: Body mass index (BMI), as an approximation of general adiposity, is an established risk factor for incidence of several adult cancer types, including colorectal cancer (CRC). There is a common perception that these relationships extrapolate directly as adverse prognostic factors after diagnosis, but evidence for this is lacking. The paper from Sclesinger et al. in this issue of the journal adds a new dimension to this debate focusing on relationships of post-diagnosis BMI (as a marker of the steady-state weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…With careful consideration of important risk and prognostic factors, the association between prediagnostic BMI and OS in all CRC patients was modest. Our most robust and consistent findings were for more extreme levels of obesity and among patient subgroups, as observed previously ( Parkin et al , 2014 ; Renehan, 2014 ; Wu et al , 2014 ). Among patients with local or locally advanced disease and among patients diagnosed aged <50 years, both class I and class II obesity were associated with a two-fold to five-fold increased risk of death as compared with overweight patients.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…With careful consideration of important risk and prognostic factors, the association between prediagnostic BMI and OS in all CRC patients was modest. Our most robust and consistent findings were for more extreme levels of obesity and among patient subgroups, as observed previously ( Parkin et al , 2014 ; Renehan, 2014 ; Wu et al , 2014 ). Among patients with local or locally advanced disease and among patients diagnosed aged <50 years, both class I and class II obesity were associated with a two-fold to five-fold increased risk of death as compared with overweight patients.…”
Section: Discussionsupporting
confidence: 90%
“…Inclusion of older patients and patients reporting weight loss appeared to attenuate or mask associations observed between obesity and OS in all CRC patients; however, none of these factors appeared to strongly impact PFS. One potential explanation is that advanced-stage patients, and similarly older patients or patients experiencing weight loss, represent a group more susceptible to the physiologic stress of cancer as well as aggressive treatment modalities, whereas, obese patients who survive the cancer experience are simply more likely to develop and die from other obesity-related causes ( Renehan, 2014 ). In a recent pooled prospective analysis of BMI and subsequent cancer risk in CRC survivors, individuals who were overweight or obese were at moderate increased risk of developing subsequent obesity-associated cancers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(6, 7, 9, 13) Further, some studies have demonstrated a U-shaped curve with potential optimal BMI in the overweight range. (14) Studies have also varied in timing of ascertainment of exposure (prior to diagnosis, at diagnosis and after diagnosis/surgery). (15)…”
Section: Introductionmentioning
confidence: 99%